EVALUASI PERAN PROFESI DAN PENGAMANAN (PROPAM) DALAM MENINGKATKAN KEDISIPLINAN PERSONIL POLRES MAGELANG - Riyanto, Riyanto; Akhmad, Jazuli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this study is to identify the role of Propam in improving the discipline of Magelang Police personnel who are not in accordance with the rules, as well as to formulate efforts to increase the role of Propam in improving the discipline of Magelang Police personnel. This research is a qualitative research, the informants in this study are 1 Waka Polres Magelang, 2 Propam personnel and 2 members of the Police Polres Magelang. The object of the research is to evaluate the role of Propam in improving the discipline of Magelang Police personnel. In processing and analyzing the data, the writer uses an interactive data model as proposed by Miles and Huberman. The result is that Propam's role in improving the discipline of Magelang Police personnel is not in accordance with the leadership's policy, with Propam personnel still not mastering their roles and functions as Propam members, limited number of Propam personnel, not all Propam personnel have vocational skills in Provos or Paminal, other factors that influence the occurrence Violations by members of the National Police are family environment, work environment, social environment, economic and character demands, lack of supervision from the unit, lack of awareness of the duties and responsibilities they carry and unfavorable environmental influences/places that should not be visited. Efforts to further increase the role of Propam in improving the discipline of Magelang Police personnel are by strengthening leadership direction activities and spiritual guidance, strengthening supervision attached to each member's activities, increasing the presence of the Propam function in activities and places prone to violations, strengthening understanding and mastery of SOPs for carrying out duties, strengthening the role of leaders and first line supervisors, taking firm action against any violations that harm the image of the Police, giving rewards to members who excel and analyzing policies for personnel who have personnel records, carrying out Operations for Enforcement of Order and Discipline for members of the Magelang Police with the goal of completeness of attributes in the use of clothing. Police service/PNS, completeness of personal data, attitude and appearance, Senpi, and early detection of drug smugglers involving members of Polri/PNS Polri in the jurisdiction of Polres Magelang.